Simplifying Expressions Warmup

Algebra Level 1

Which expression is equivalent to:

4 ( x ( 3 ( x ( 2 ( x + 1 ) ) ) ) ) ? 4(x(3(x(2(x + 1)))))?

24 x 3 + 12 x 2 24x^3 + 12x^2 24 x 3 + 24 x 2 24x^3 + 24x^2 12 x 3 + 24 x 2 12x^3 + 24x^2 12 x 3 + 12 x 2 12x^3 + 12x^2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Brilliant Mathematics Staff
Aug 1, 2020

We can simplify this expression by beginning our distributing at the inner-most parentheses:

4 ( x ( 3 ( x ( 2 ( x + 1 ) ) ) ) ) = 4 ( x ( 3 ( x ( 2 x + 2 ) ) ) ) = 4 ( x ( 3 ( 2 x 2 + 2 x ) ) ) = 4 ( x ( 6 x 2 + 6 x ) ) = 4 ( 6 x 3 + 6 x 2 ) = 24 x 3 + 24 x 2 \begin{array} { r c l } 4(x(3(x(2(x + 1))))) &=& 4(x(3(x(2x + 2)))) \\ &=&4(x(3(2x^2 + 2x))) \\ &=&4(x(6x^2 + 6x)) \\ &=& 4(6x^3 + 6x^2) \\ &=& 24x^3 + 24x^2 \end{array}

Exactly how I did it! @Brilliant Mathematics

Yajat Shamji - 10 months, 2 weeks ago

Me too! This is distribution 5 5 times!

Lâm Lê - 9 months, 1 week ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...